Practical Recommendations for Preoperative Skin Antisepsis - Carlos Arturo Álvarez; Cesar Ernesto Guevara; Sandra Liliana Valderrama; Carlos Fernando Sefair; Jorge Alberto ortes; María Fernanda Jimenez; Carmen Gabriela Soria; Luis Ernesto Cuellar
Abstract The search for strategies for the reduction of Surgical Site infection (SSI) is a priority, given the impact those infections have on the outcome of the patients. The preope rative patient skin antisepsis, has recently gained greater significance in the prevention of SSI, as one of the critical factors, which can be intervened and can reduce the risk of infection. In recent years, comprehensive investigations have been published, not only dedicated to the comparison of antiseptic solutions, application techniques, but also about the importance of preoperative washing, use of surgical tapes and dressings impregnated with antiseptics, and preoperative shaving. This review outlines the key findings related to the preoperative patient's skin antisepsis and offers a protocol with practical recommendations to be implemented in the institutions of our country. It provides evidence based recommendations about the use of antiseptic solutions (povidone iodine, chlorhexidine, chlorhexidine plus alcohol, etc.) with emphasis on the advantages and disadvantages of each one.